Makna Tanda Budaya Batak pada Film "Ngeri-Ngeri Sedap" - Salsabila; Alex Sobur (Bandung Conference Series: Communication Management, 2023)
Abstract. Abstract. The research entitled “The Meaning of Batak Cultural Signs in the Film `Ngeri-Ngeri Sedap`” is motivated by Indonesia which has a variety of cultures, so that not a few Indonesian people do not know about other cultures that are far from everyday life. The purpose of this study is to find out the meaning of the signs contained in the film which will later take the required scene cuts. First, the level of reality which gets the meaning of Batak culture starting from Pak Domu who often visits the lapo, the traditional head covering of the Batak uis culture. Second, the level of representation where aspects of Batak culture can be seen from the average shooting technique using close-up medium to show the expressions or gestures of the film actors. Finally, aspects of Batak culture which can be seen from the ideological level, namely the patriarchal social system that exists within Pak Domu as the head of the family dominates all decisions to be made by family members. Abstrak. Penelitian berjudul “Makna Tanda Budaya Batak pada Film `Ngeri-Ngeri Sedap`” dilatarbelakangi oleh Indonesia yang memiliki ragam akan kebudayaannya, sehingga tidak sedikit masyarakat Indonesia tidak mengetahui kebudayan lain yang jauh dari kehidupan sehari-hari. Tujuan dari penelitian ini adalah untuk mengetahui makna tanda yang terkandung dalam film yang nantinya akan mengambil potongan scene yang dibutukan. Pertama, level realitas yang dimana mendapatkan makna budaya batak mulai dari Pak Domu yang sering mengungjungi lapo, kain penutup kepala khas budaya Batak uis. Kedua, level representasi yang dimana aspek budaya batak terlihat dari tenik pengambilan gambar rata-rata menggunakan medium close-up untuk memperlihatkan ekspresi ataupun gesture pemeran film tersebut. Terakhir, aspek budaya batak yang terlihat dari Level ideologi, yaitu sistem sosial patriarki yang ada dalam diri Pak Domu selaku kepala keluarga mendominasi seluruh keputusan yang akan di ambil oleh anggota keluarga.